One city, different views: an analysis of cultural schemes on Brussels as a living environment. Issue 2 (15th March 2022) - Verhoest, Pascal; Bauwens, Joke; te Braak, Petrus
ABSTRACT: Brussels is struggling with a negative image as a living environment. This converges with an outward migration of economically better-off inhabitants, which has a negative effect on tax revenues. Improving the image of Brussels has thus become a policy priority. This paper investigates perceptions about Brussels within three subpopulations: Brussels residents, commuters and non-residents. By applying cluster analysis to 180 interviews, distinctive patterns in the perceptions are found. These findings suggest that beliefs about Brussels are both mediated by people's affinity with the city and resonate with ingrained urban and anti-urban ideologies. Lessons for policy and place marketing are drawn.